Muslim women leaders in Malaysian universities: Managing identities, power & institutions - Ismail, Habibah; Baharun, Hazleena; A. Jalil, Suhaili; Ahmad, Sakinah; Idrus, Mohd Muzhafar; Harun, Haliza (‘Abqari Journal, 2025)
Women leaders face persistent challenges in balancing work-life demands and navigating masculine-centric environments. This study examines women in top leadership positions within Malaysian private higher education institutions (HEIs). It aims to: (1) investigate the gender composition of HEI leadership; (2) explore the challenges and enablers experienced by women leaders; and (3) examine the language and communication skills employed by these leaders. Document analysis of leadership composition was conducted, followed by discourse analysis of the interviews. Findings reveal that their identity as Muslim and their gendered roles (as wife, mother) substantially shape their leadership practices. Effective negotiation with partners, requiring strong communication skills, is crucial for balancing professional and personal lives. This highlights the impact of gender and religious roles on women leaders. The study contributes to understanding women leaders' experiences, best practices, and the conceptualization of specific factors affecting Muslim women leaders. This research contributes theoretically by deepening our understanding of the complex interplay between gender and religious identity in shaping leadership experiences within the Malaysian HEI context. Practically, it offers insights that can inform the design of more inclusive development programs and institutional support mechanisms tailored to the needs of Muslim women in higher education institutions.